Ethical issues in communication in a tertiary oncology center: exploratory survey - Ruggiero, Elena; Schiavon, Stefania; Stragliotto, Silvia; Gallio, Ivan; Formaglio, Fabio; Lorusso, Marina; Feltrin, Alessandra; Maruzzo, Marco; Brunello, Antonella (Frontiers in Psychology, 2025)
BackgroundDespite evidence of its importance, communication in oncology remains a critical challenge, especially in case of bad news. The doctor-patient relationship is often strained by time limitations, emotional challenges, and cultural or ethical dilemmas surrounding end-of-life discussions. This study examines barriers to effective communication at the Veneto Institute of Oncology (IOV), focusing on time constraints and emotional difficulties in clinical practice. It aims to identify factors hindering timely and effective discussions on bad news and end-of-life issues, the primary participants in such conversations, and reasons for delays in addressing sensitive topics.Materials and methodsAn anonymous questionnaire was completed by 43 attending physicians from Oncology and Haemato-oncology departments at the IOV, with 69.8% of the respondents being women. The majority of the respondents were under 40 years of age. Data on demographics, roles, and communication practices were analysed to identify behavioral patterns.ResultsMost respondents (65.1%) prioritized communicating bad news to patients rather than caregivers. Time constraints were the most reported barrier (40%), followed by emotional distress, fear of demotivating patients, and insufficient training. Despite challenges, 76.7% felt confident in shared decision-making with patients.ConclusionThe study highlights the need for structured communication training and better resources to address time and emotional barriers, to enhance patient autonomy and to reinforce doctor-patient relationships in end-of-life care.